Spin-Orbit Coupling Effects in AumPtn Clusters (m + n = 4) (2016)
A study of AumPtn(m + n = 4) clusters with and without spin–orbit (SO) coupling using scalar relativistic (SR) and two component methods with the ZORA Hamiltonian was carried out. We employed the PW91 functional in conjunction with the all-electron TZ2P basis set. This paper offers a detailed analysis of the SO effects on the cluster geometries, on the LUMO–HOMO gap, on the charge distribution, and on the relative energies for each relativistic method. In general, SO coupling led to an energetic rearrangement of the species, to changes in geometries and structural preferences, to changes in the structural identity of the global minimum for the Au3Pt, AuPt3 and Pt4 cases, and to a reduction of relative energies among the clusters, an effect that appears stronger as the amount of Pt increases.